Implementation of a Web-Based Decision Support System Using Simple Additive Weighting (SAW) For Assessment Of “Siswa Berprestasi” In Sumenep High Schools - Najib, Muhammad (International Journal of Science, Engineering, and Information Technology, 2024)
The assessment of student achievement in schools is a crucial aspect of determining educational success. This research developed a web-based Decision Support System (DSS) utilizing the Simple Additive Weighting (SAW) method to evaluate outstanding students, known as “Siswa Berprestasi,” in several high schools in the Sumenep region. Data were collected from 30 respondents via online questionnaires. The validity and reliability of the data collection instruments were tested using construct validity and Cronbach’s Alpha reliability tests. The results indicate that the SAW method effectively assesses student performance by considering academic, non-academic, and extracurricular criteria. The DSS implemented in case studies across five high schools in Sumenep showed significant improvements in assessment transparency and accuracy. The findings suggest the SAW-based DSS enhances the quality of student evaluations and is recommended for broader adoption in schools across the region.